2013
DOI: 10.1007/s12663-013-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction Audit of Patients Undergoing Mandibular Distraction Osteogenesis with Extra-Oral Distraction Appliances

Abstract: Introduction The aim of this research was to evaluate the level of satisfaction of patients who were undergoing distraction osteogenesis of mandible with extraoral distraction appliance. Material and Methods The prospective study was performed on 13 patients with facio-mandibular deformity reporting to the Oral Health Sciences Center, PGIMER, Chandigarh, India, who required surgical and orthodontic intervention for correction. A standardized multiple choice questionnaire was provided to all patients at 3 stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…In Datta et al [ 7 ] about 53.84% of the study group readily accepted the extraoral appliance, while the others had some apprehension regarding the bulk and esthetics. In our study group, 100% of the study group accepted the extraoral device.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Datta et al [ 7 ] about 53.84% of the study group readily accepted the extraoral appliance, while the others had some apprehension regarding the bulk and esthetics. In our study group, 100% of the study group accepted the extraoral device.…”
Section: Discussionmentioning
confidence: 99%
“…But the rate of patients experiencing transient numbness of the lower lip varied widely in all studies. While Datta et al reported 76% patients experiencing this complication, only 14% had transient numbness in the study group of Primrose et al [ 7 , 11 ]. In our group 16% of patients experienced this complication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations